Andika Satria Yoga S Konsep Learning Experience dalam Kerangka Filsafat Konstruktivis John Dewey: Konsep Learning Experience dalam Kerangka Filsafat Konstruktivis John Dewey - Suharno, Andika Satria Yoga (UPT Perpustakaan Universitas Jambi, 2026)
Contemporary learning is still largely dominated by a knowledge transmission approach that positions learners as passive recipients, resulting in learning processes that are often less meaningful and disconnected from learners’ real-life experiences. This article aims to examine the concept of learning experience within the framework of John Dewey’s constructivist philosophy and its contribution to meaningful learning. This study employs a literature review method with a philosophical–qualitative approach, drawing on John Dewey’s major works and relevant national and international educational journals. Data were analyzed using content analysis and interpretative techniques to examine conceptual consistency, interconnections among ideas, and their relevance to contemporary educational contexts. The findings indicate that learning experience in Dewey’s thought is understood as an active, reflective, and continuous process of reconstructing experience, operating through the principles of continuity and interaction. This concept positions learners as active subjects in the construction of knowledge, while the social environment and contextual settings serve as primary sources of learning. The article underscores the enduring relevance of John Dewey’s philosophy as a foundational framework for the development of experience-based learning in addressing contemporary educational challenges.